Hubungan Budaya Organisasi Dengan Perilaku Birokrasi: Studi Kasus Pada Pemerintah Kabupaten/ Kota di Sulawesi Selatan - Burhanuddin Abubakar (Jurnal Borneo Administrator, 2009)
This research aims to analize the relationship of organizational culture to the bureaucrat behaviors . Bureaucrat behavioural patterns are differentiated in autocratic behaviour, custodial behaviour, supportive behaviour and collegial behaviour. Autocratic behaviour is a behaviour which focuses on self oriented, authority power, loyality, obidience, and priority to fulfill basic needs. Custodial behaviours is a behaviour which depends on economic resources of  an organisation, solidarity, familiarity. Supportive behaviour is a bureaucrat behavior which give strong support on achieving organizational goals and objectives. Collegial behaviour is a behaviour which parallelly focus on performance, familiarity, and solidarity in achieving organizational goals.  The result of the research  shows that organizational culture  has relationship to autocratic behaviour, custodial behaviour, supporting behaviour and collegial behaviour. Based on contribution, communal culture factor has strong contibution to form supportive and collegial behaviours. Generally, Bureaucrat behavioural patterns of municipality and regency is transitional behaviours that is  still practicing traditional behaviours    with autocratic and custodial behaviour, and the other side bureaucrat behavioural patterns have oriented to modern  bureaucrat behaviour which practice supportive and collegial behaviours.  Key Words: Budaya Organisasi, Perilaku Organisasi, Pemerintah Kabupaten/ Kota